2019
DOI: 10.1371/journal.pone.0222840
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiological role of prostanoids in coagulation of the portal venous system in liver cirrhosis

Abstract: BackgroundProstanoids are important regulators of platelet aggregation and thrombotic arterial diseases. Their involvement in the development of portal vein thrombosis, frequent in decompensated liver cirrhosis, is still not investigated.MethodsTherefore, we used pro-thrombotic venous milieu generation by bare metal stent transjugular intrahepatic portosystemic shunt insertion, to study the role of prostanoids in decompensated liver cirrhosis. Here, 89 patients receiving transjugular intrahepatic portosystemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…The same authors found an association between elevated levels of thromboxane B2 in the portal circulation and portal hepatic venous pressure gradient. They concluded that thromboxane B2 is possibly associated with prothrombotic potential [63]. In the paper by Eyraud et al [52], soluble P selectin decreased after liver transplantation, suggesting a higher soluble P selectin/platelet count ratio in cirrhotic patients before transplantation.…”
Section: Soluble Release Markersmentioning
confidence: 97%
“…The same authors found an association between elevated levels of thromboxane B2 in the portal circulation and portal hepatic venous pressure gradient. They concluded that thromboxane B2 is possibly associated with prothrombotic potential [63]. In the paper by Eyraud et al [52], soluble P selectin decreased after liver transplantation, suggesting a higher soluble P selectin/platelet count ratio in cirrhotic patients before transplantation.…”
Section: Soluble Release Markersmentioning
confidence: 97%
“…COXs generate prostanoids, and several have contractile effects on smooth muscle 50 . Prostaglandin E 2 is found in portal vein 55 . We tested the effect of prostaglandin E 2 and observed concentration‐dependent contraction (Figure 4D).…”
Section: Resultsmentioning
confidence: 95%
“… 50 Prostaglandin E 2 is found in portal vein. 55 We tested the effect of prostaglandin E 2 and observed concentration‐dependent contraction (Figure 4D ). The EC 50 for the prostaglandin E 2 effect is 4 μM (Figure 4D ).…”
Section: Resultsmentioning
confidence: 99%
“…In agreement, AA was increased in the liver of colitis mice suggesting that GLA and DGLA are potentially used as precursors for AA production, skewing the DGLA/ AA balance to support inflammation (64, 65). Furthermore, this study putatively identified prostaglandin G2 (PGG2), an AA derivative, as being increased in the colitis liver and has been implicated as a pathophysiological factor in liver cirrhosis by promoting platelet aggregation and thrombosis (66). Therefore, the bidirectional liver-gut axis may exacerbate inflammation and tissue damage in both organs via AA production and conversion to small metabolites meaning the disappearance of the precursor GLA could be used as a biomarker of systemic disease progression (65, 67).…”
Section: Discussionmentioning
confidence: 99%